2021
DOI: 10.3961/jpmph.20.293
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Quitting Smoking in Indonesia

Abstract: Objectives: The aim of this study was to identify factors associated with quitting smoking in Indonesia Methods: Data on 11 115 individuals from the fifth wave of the Indonesia Family Life Survey were analyzed. Quitting smoking was the main outcome, defined as smoking status based on the answer to the question “do you still habitually (smoke cigarettes/smoke a pipe/use chewing tobacco) or have you totally quit?” Logistic regression was performed to identify factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Further, our one-year smoking cessation percentage of around 15% was in line with the report in India (14.2%) [ 27 ] and Indonesia (12.3%) [ 28 ], but slightly lower than that reported in high-income nations like the USA (over 25.0%) [ 29 ], and Poland (30.4–37.9%) [ 30 ]. The difference might be driven by differences in (1) assessment of the smoking behaviours (smoking duration, nicotine dependence, stage of addiction), (2) the availability of cessation support programs, and (3) the level of tobacco control policies implemented in each country.…”
Section: Discussionsupporting
confidence: 91%
“…Further, our one-year smoking cessation percentage of around 15% was in line with the report in India (14.2%) [ 27 ] and Indonesia (12.3%) [ 28 ], but slightly lower than that reported in high-income nations like the USA (over 25.0%) [ 29 ], and Poland (30.4–37.9%) [ 30 ]. The difference might be driven by differences in (1) assessment of the smoking behaviours (smoking duration, nicotine dependence, stage of addiction), (2) the availability of cessation support programs, and (3) the level of tobacco control policies implemented in each country.…”
Section: Discussionsupporting
confidence: 91%
“…The findings suggested that male adolescents are more likely to be in both the contemplation and action phases as compared to maintenance phase. Similarly, prior research on smoking cessation among Indonesian adolescents has noted a greater tendency toward quitting smoking and maintaining a free smoke life among females (16,17). In Indonesia, Indonesian men rank first in countries with a prevalence of smokers in the world at 63%, while only 5% of Indonesian women are smokers, making smoking the majority behavior of Indonesian men (18).…”
Section: Discussionmentioning
confidence: 87%
“…This high number of adolescents needs the attention of health practitioners because smoking causes various cancers and also reduces academic achievement. Furthermore, nicotine causes addiction, which makes it difficult to quit smoking (Sadarang, 2021).…”
Section: Research Articlementioning
confidence: 99%